Krasoslovje v razvojnih izzivih na krasu [2] = Karstology and Development Challenges on Karst - Culver, David C.; Debevec, Bogdan; Zupan Hajna, Nadja; Knez, Martin; Kovačič, Gregor; Kranjc, Andrej; Mulec, Janez; Pipan, Tanja; Prelovšek, Mitja; Ravbar, Nataša; Semeja, Aleš; Slabe, Tadej; et al. (ZRC SAZU, Založba ZRC, 2022)
The second book in the new collection Karstology in Development Challenges in the Karst brings together the findings obtained in planning and construction of motorways in the Karst. More than 350 new caves were opened up in the final wave of construction. This was followed by studies on arranging karstic features for tourism and their management. We also selected studies on karstic ecology, in which we made use of biological and microbiological research. At the end there is a summary of everything we need to take into account in planning different encroachments in karstic areas.